If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2x + -3) = 2(8x + 1) Reorder the terms: 8(-3 + 2x) = 2(8x + 1) (-3 * 8 + 2x * 8) = 2(8x + 1) (-24 + 16x) = 2(8x + 1) Reorder the terms: -24 + 16x = 2(1 + 8x) -24 + 16x = (1 * 2 + 8x * 2) -24 + 16x = (2 + 16x) Add '-16x' to each side of the equation. -24 + 16x + -16x = 2 + 16x + -16x Combine like terms: 16x + -16x = 0 -24 + 0 = 2 + 16x + -16x -24 = 2 + 16x + -16x Combine like terms: 16x + -16x = 0 -24 = 2 + 0 -24 = 2 Solving -24 = 2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -16-6x=14x-9x | | X/5-4=7/8 | | -3(6x-6)+9=-18x+27 | | 4x-z=yforx | | 2x/3+4=-5 | | 9x+3=2(4x-1)+5 | | x^2+10x-3=4 | | 9(x+2)-2=24-4x-8+13x | | 15w-25+16-12w= | | -5+9(x-5)=13x+5-4x | | 9x-28= | | X=12x+2 | | x^2=8x+4 | | 11n-9-10n-6=8 | | -1/6(x-18)+1/2(x+2)=x+28 | | (x-3)+38=-4x | | (x-3)+38=-4 | | 3-7x=21+x | | 3(x-7.2)=3.3 | | 53+24+-5w=102 | | X/11+3=-12 | | 2x-30x-4=0 | | t-10=-5 | | -2(4x-2)-2x=22 | | n^2+30n+120=0 | | 7x+35=11x+35 | | (-4x^2+9x)+(14x^2-2x-3)= | | X/11+4=-8 | | 2.9(x+3.1)=6.9 | | 5x-4(9-3x)=-2 | | x-6=3y | | 18x^2-45=0 |